Rethinking Value Chains: Tackling the Challenges of Global Capitalism - Florence Palpacuer; Alistair Smith (Policy Press, 2021)
Today, production processes have become fragmented with a range of activities divided among firms and workers across borders. These global value chains are being strongly promoted by international organizations, such as the World Bank and the World Trade Organization, but social and political backlash is mounting in a growing variety of forms. This original volume brings together academics and activists from Europe to think creatively about the social and environmental imbalances of global production and how to reform the current economic system.
Keywords: 330; Academic activism; Capitalism; Co-creation; Global value chains; Sustainability; sustainable growth